Tingkat Kepuasan Pengunjung pada Daya Tarik Ekowisata dan Edukasi Green Talao Park di Kabupaten Padang Pariaman - Anisa Febriani Putri; Feri Ferdian; Azmen Kahar (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This research was motivated by problems regarding visitor dissartisfaction with existing attractions, inadewuate acces, unavailability of souvenir and souvenir sellers, lack of health facilities and inadequate maintenance of available facilities.This type of research is classified into quantitative descriptive with a causal associative approach. The sampling technique used in this study is a non-probability sampling technique with purposive sampling. The number of samples used amounted to 379 people. The data collection technique was carried out by distributing questionnaires using a Likert scale that has been tested for validity and reliability. Data processing was carried out using the continuum line method. Based on the research conducted, the following results were obtained: The level of satisfaction in terms of the attraction indicator with an average acquisition of 2.43 in the dissatisfied category, The level of satisfaction in terms of accessibility indicators with an average acquisition of 2.42 in the unsatisfied category satisfied, the satisfaction level in terms of facility indicators with an average acquisition of 2.21 with the dissatisfied category, and the satisfaction level in terms of supporting service indicators with an average acquisition of 2.43 with the dissatisfied category